Necessity knows no law in a snail. Issue 1 (1st January 2017) - Ito, E.; Totani, Y.; Oike, A.
Abstract: In the present review, we outline the relationship between starvation and taste-aversive learning (conditioned taste aversion: CTA) in the pond snail Lymnaea stagnalis and introduce the â€œnecessity knows no lawâ€ concept. When snails were food-deprived for a short period, the snails learned and formed memory of CTA well, whereas when snails were food-deprived for a prolonged period, the snails appeared not to learn CTA or form long-term memory (LTM) of it. However, in severely food-deprived snails (i.e. snails that were food-deprived for a prolonged period), memory was found to indeed form but was overpowered by the effect of severe food deprivation. That is, snails are partially restricted in the â€œnecessity knows no lawâ€ concept. Moreover, this CTA-LTM was context dependent and was observed only when the snails were in a context similar to that in which the training occurred. In addition, when insulin was injected into the severely food-deprived snails, they started to exhibit learning and memory. That is, insulin rescued the snailsâ€™ â€œhiddenâ€ ability of memory retrieval. In addition to these topics in snails, we survey the literature on starvation and learning obtained in other animals for general discussion. We hope that this review will stimulate further detailed studies of motivation in invertebrates.